ANALYSIS THE PERFORMANCE APPRAISAL EFFECTIVENESS ON EMPLOYEE PERFORMANCE AT PT. PELINDO IV (PERSERO) BITUNG - Nanggala, James Adi (Jurnal Berkala Ilmiah Efisiensi, 2016)
ABSTRACT This study focus on the effectiveness of the Performance Appraisal system. Performance Appraisals are an imperative part of HRM systems within company. Performance Appraisal is known to benefit company by helping them measure performance, motivate employees and most commonly help to make HR related administrative decisions such as promotions and rewards. This study aims to investigate the effectiveness of Performance Appraisals from the perception of the employees. The study was carried out in PT Pelindo IV Bitung. The data were gathered from the employees to measure their opinions of the PA system and how successful they feel it. The study revealed that overall the employees were happy with having to complete performance appraisal, but there is still some work to be done in improving the system and making it more successful and rewarding. Keywords: Human Resource, Performance Appraisals, Performance Appraisal.